RENCANA PELAKSANAAN PEMBELAJARAN DIGITAL PERANGKAT PEMBELAJARAN GURU 4.0 - Nurchaili (Direktorat GTK Madrasah Ditjen Pendis Kementerian Agama Republik Indonesia, 2021)
Lesson Plan (RPP) is one of the mandatory learning tools that must be compiled bythe teacher. Whether the learning is good or not, one of them is determined by thequality of the planning described by the teacher in the lesson plan. Digital RPP is oneform of teacher self-development in the face of 21st century learning and theIndustrial Revolution 4.0. which is also called the era of disruption. Teacher 4.0 is acreative and innovative teacher who is able to make learning devices in digital formatand can keep up with the times. Digital RPP is one of the opportunities for teachersto answer the challenges of the disruption era. Digital RPP is a complete package oflearning activities and powerful, because it contains a learning plan that isequipped with teaching materials, both text, image and video learning, onlinequestions and links subject matter that can be accessed directly from the RPP.Digital RPP is easily revised, low-cost, attractive and easily shared, and can beaccessed anywhere and anytime.